Mídias sociais e cocriação de valor: Análise sobre práticas cocriativas no contexto de uma organização sem fins lucrativos - Carvalho, Fabiana Miranda Reis de (2018)
The SD-Logic is an approach in which service is the basis of the system of exchanges. At the heart of this approach lies the assumption that value creation is established through interaction among companies, customers and other stakeholders. In this environment, companies are pressured to take a more participatory approach, which has been greatly facilitated by online communities hosted on social media. These platforms have assumed unprecedented importance for the communication among customers and organizations, whether they are commercial or not and are conducive channels to value co-creation. Since the SD-Logic perspective outweighs the traditional commodity exchange paradigm, the study analyzed the value co-creation in an online community of an internationally known nonprofit organization and its relationship towards community’s engagement and to the brand’s loyalty. The research took into account the representativeness of nonprofits organizations to society, and the broadening of the challenges to attract and retain volunteers. To reach the proposed goal, a survey was conducted with 534 community members. The collected data were analyzed using the structural equation modeling (SEM), with estimation of the Partial Least Squares - Path modelling (PLS-PM), through the tools offered by SmartPLS 3 software. The results supported the conceptual model of value co-creation in online communities of NPOs, indicating that community members base their value assessments on three elements: Experience, Interpersonal Interaction, and Social Relationships. These elements significantly explained the commitment towards the community and to the brand’s loyalty, validating the importance of this marketing strategy also in the NPO context. Theoretical and practical implications of these outcomes are discussed, as well as the limitations and indications for future researches.